Who Fills Institutional Voids? Entrepreneurs' Utilization of Political and Family Ties in Emerging Markets. (November 2019) - Ge, Jianhua; Carney, Michael; Kellermanns, Franz
How do entrepreneurs fill institutional voids that prevail in emerging markets? By incorporating insights from both the political and family embeddedness perspectives, we argue that both political ties and family ties can compensate for gaps in the institutional infrastructure of emerging markets. Specifically, we propose and examine the partial substitutability of family ties for political ties as a means of filling institutional voids. Our empirical work based on Chinese private enterprises strongly supports this argument. We also find that the effective utilization of family ties is contingent on both family members' motivation (willingness to use resources for the firm) and entrepreneurs' mobilization (authority in the family to mobilize family members). This study bridges the literature on political ties and family ties to understand their respective costs and benefits and therefore advances our understanding of entrepreneurs' networking strategies in emerging markets.